HCO+ (Encyclopedia of Astrobiology, 2015)
Purpose of review Antithrombotic therapy for patients with atrial fibrillation (AF) after acute coronary syndrome (ACS) or percutaneous coronary intervention (PCI) requires balancing prevention of stroke and coronary events against bleeding. Recent recurrent-event and patient-centered analyses of AUGUSTUS make this review timely by reframing treatment benefit beyond first events. Recent findings Four dedicated trials support dual antithrombotic therapy with direct oral anticoagulants (DOAC) plus P2Y12 inhibitor and early aspirin withdrawal to reduce bleeding without significant increase in ischemic events. However, aspirin-free strategies differ by anticoagulation indication: in patients without anticoagulation, very early aspirin withdrawal after ACS or PCI may increase the risk of coronary events, whereas in patients with AF receiving anticoagulation, oral anticoagulation may assume the early antithrombotic role of aspirin. AUGUSTUS showed that apixaban and placebo each reduced bleeding compared with vitamin K antagonist and aspirin. The recent total-event analyses further showed lower cumulative bleeding with apixaban than with vitamin K antagonist, and substantially greater cumulative bleeding with randomized aspirin than with placebo, along with similar total ischemic events and hospitalizations. Summary For patients with AF after ACS or PCI, DOAC-based dual antithrombotic therapy provides the most favorable cumulative safety-efficacy balance. Future research should focus on the timing of aspirin discontinuation and validate recurrent-event endpoints.